2020
DOI: 10.3389/fpsyg.2020.00969
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validity of the Fear of Water Assessment Questionnaire

Abstract: Fear of water is the strongest predictor for no or low swimming competencies. Some individuals will never learn to swim due to their complete avoidance of water, whereas others might have difficulty with learning due to the fact that they cannot sufficiently relax their body to facilitate floating or swimming. Therefore, it is important to identify these people and to establish effective teaching strategies that can best help this specific population. Recognizing this, there is a clear need for an assessment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 29 publications
2
17
0
3
Order By: Relevance
“…Swimming teachers and coaches have commonly noted that the most common mistakes in backstroke swimming are holding the head too high and adopting a sitting position (Stibilj et al, 2020), usually because of the non-swimmer’s fear of water. Indeed, individuals classified as having a fear of water strongly disagreed and agreed, respectively, with the statements “I am able to push from the wall and glide on the surface,” and “When I am in a pool, I am afraid when I am not in contact with floor” (Misimi et al, 2020). Use of goggles (no snorkel was used during back gliding exercises) helped our young participants, with fear of water, place their heads in the correct horizontal position, perhaps giving them increased opportunities to adopt a correct posture and develop back gliding skills than our NGS participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swimming teachers and coaches have commonly noted that the most common mistakes in backstroke swimming are holding the head too high and adopting a sitting position (Stibilj et al, 2020), usually because of the non-swimmer’s fear of water. Indeed, individuals classified as having a fear of water strongly disagreed and agreed, respectively, with the statements “I am able to push from the wall and glide on the surface,” and “When I am in a pool, I am afraid when I am not in contact with floor” (Misimi et al, 2020). Use of goggles (no snorkel was used during back gliding exercises) helped our young participants, with fear of water, place their heads in the correct horizontal position, perhaps giving them increased opportunities to adopt a correct posture and develop back gliding skills than our NGS participants.…”
Section: Discussionmentioning
confidence: 99%
“…We asked them to complete the Fear of Water Assessment Questionnaire (Misimi et al, 2020). Misimi et al (2020) found that this instrument is a valid 20-item scale that effectively identifies people with fear of water (Cronbach’s alpha was 0.831). See Table A6 in the Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…Vandens baimei atpažinti yra kuriamos įvairios vertinimo priemonės, klausimynai (Misimi et al, 2020). Minėti autoriai, vystydami ir validuodami vandens baimės klausimyną, išskiria tris su vandens baime susijusius faktorius: sąlytis su vandens aplinka, natūrali vandens jėga ir judesio valdymas vandenyje.…”
Section: Diskusijaunclassified
“…Vaikų tyrimo duomenys atskleidė, kad vaikai turi didžiulę baimę pradėti plaukti be pagalbinių plaukimo priemonių. Vienas būdas sumažinti stresą ir nerimą esant vandenyje yra akinių ar kaukės naudojimas, kas suteikia galimybę atmerkti akis po vandeniu ir taip palengvinti veido panardinimą į vandenį (Kapus et al, 2018;Misimi et al, 2020). Taigi, anot F. Misimi ir kt.…”
Section: Diskusijaunclassified
See 1 more Smart Citation